2016
DOI: 10.1590/s1984-82502016000100011
|View full text |Cite
|
Sign up to set email alerts
|

Level of satisfaction of clients of public pharmacies dispensing high-cost drugs in Espírito Santo, Brazil

Abstract: The aim of this study was to evaluate the level of satisfaction of pharmaceutical services and to determine the socioeconomic profile of public pharmacy clients. This is a cross-sectional observational study using a quantitative approach. The sample was calculated from the monthly number of patients seen in pharmacies and was stratified for each pharmacy. Data were analysed using SPSS 11.5 software and by observing the simple relative frequencies for qualitative variables. For the quantitative variables, the a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
1
0
2

Year Published

2017
2017
2022
2022

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 18 publications
1
1
0
2
Order By: Relevance
“…In this sense, our data revealed the fragility in the pharmaceutical-patient relationship; this is consistent with the data reported by Cassaro et al (2016), who also found low scores for the clinical performance of pharmacists in SUS' public pharmacies.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…In this sense, our data revealed the fragility in the pharmaceutical-patient relationship; this is consistent with the data reported by Cassaro et al (2016), who also found low scores for the clinical performance of pharmacists in SUS' public pharmacies.…”
Section: Discussionsupporting
confidence: 92%
“…The level of satisfaction was expressed for each question and for the questionnaire as a whole. Users were also classified as satisfied (score equal to or greater than 4) and not satisfied (score less than 4) (Cassaro et al, 2016). The interviews were not conducted by the researcher, but by a person trained for that purpose.…”
Section: Evaluation Of User Satisfaction and Perception Regarding The...mentioning
confidence: 99%
“…Em relação ao gênero, a maioria dos participantes era representada por mulheres, 93 (63,7%), e 53 (36,3%) eram homens. Do mesmo modo, evidência demonstra que os cuidados com a saúde são mais importantes para mulheres que para os homens, o que pode explicar a maior frequência destas (Cassaro et al, 2016). Research, Society and Development, v. 11, n. 8, e48211831217, 2022 (CC BY 4.0) | ISSN 2525-3409 | DOI: http://dx.doi.org/10.33448/rsd-v11i8.31217 6 A presença de comorbidades foi verificada em 67 usuários (45,9%), sendo o diabetes a mais observada, 46 (68,7%), seguida de hipertensão, 33 (49,3%) e em 17 usuários a associação de ambas.…”
Section: Dados Dos Usuáriosunclassified
“…Ainda que o farmacêutico atue clinicamente provendo cuidados que contemplem a revisão da farmacoterapia e orientações ao paciente relacionadas ao tratamento medicamentoso (Liu et al, 2020), muitas vezes não está preparado para fornecer assistência clínica (Wang et al, 2020), em especial no sistema público de saúde brasileiro (Cassaro et al, 2016;Bonadiman et al, 2017). Tal fato resulta em insatisfação de pacientes com os serviços farmacêuticos (Cruz, 2017).…”
Section: Introductionunclassified